Without honor or decency: Discourse and representation on prostitution in Mexico: 1890-1910 - Bracamonte Allaín, Jorge (1998)
The members of the literate and scientific elite of the Porfiriato, as in the case of Julio Guerrero, shared the idea that sin was insufficient to define and define and guide human behavior. This is not a casual event, they all participated in the same experience: that of the definitive exhaustion of a paradigm of knowledge whose foundations were rooted in a religious conception of life and the world. These men, formed in the context of secularization and the triumph of the liberal State over the Church, became at the end of the 19th century the reductive conscience of a State that sought to redeem Mexican society from backwardness and a supposed moral debacle.